2021
DOI: 10.3390/molecules26237171
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenicity of Tectona grandis Wood Extracts and Their Ability to Improve Carbohydrate Yield for Kraft Cooking Eucalyptus Wood

Abstract: Considering the toxicity of the impurities of synthesized anthraquinone, this study clarified new catalytic compounds for kraft cooking with improved carbohydrate yield and delignification and less mutagenicity, which are important for ensuring the safety of paper products in contact with food. The 2-methylanthraquinone contents of teak (Tectona grandis) woods were 0.18–0.21%. Acetone extracts containing 2-methylanthraquinone from Myanmar and Indonesia teak woods as additives improved lignin removal during kra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…AQ is reduced to anthrahydroquinone (AHQ) by carbohydrates in the wood, and the product is oxidized back to the anthraquinone through a reaction, which involves reducing the active site (ß- O -4) in lignin during alkaline cooking [ 24 ]. Several studies also reported the benefits of AQ addition in pulping, namely a lower kappa number and improved pulp yield for kraft/soda cooking of hardwood and non-wood materials [ 25 , 26 , 27 , 28 ]. Utami et al [ 29 ] revealed the advantages of prehydrolysis followed by soda with soluble anthraquinone (soda-SAQ) cooking over kraft cooking for Acacia crassicarpa , namely a higher pulp yield of 1.8% and a higher brightness level by 3.8–3.9 points.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…AQ is reduced to anthrahydroquinone (AHQ) by carbohydrates in the wood, and the product is oxidized back to the anthraquinone through a reaction, which involves reducing the active site (ß- O -4) in lignin during alkaline cooking [ 24 ]. Several studies also reported the benefits of AQ addition in pulping, namely a lower kappa number and improved pulp yield for kraft/soda cooking of hardwood and non-wood materials [ 25 , 26 , 27 , 28 ]. Utami et al [ 29 ] revealed the advantages of prehydrolysis followed by soda with soluble anthraquinone (soda-SAQ) cooking over kraft cooking for Acacia crassicarpa , namely a higher pulp yield of 1.8% and a higher brightness level by 3.8–3.9 points.…”
Section: Introductionmentioning
confidence: 99%
“…There are only a few studies on the potential of totally chlorine-free (TCF) bleaching with peroxymonosulfuric acid (P sa ) to produce high-quality dissolving pulp [ 23 , 24 , 25 ]. Soda-SAQ cooking and TCF bleaching are considered environmentally friendly due to the sulfur-free process in the cooking and reduction in the halogenated organic compounds emissions during bleaching [ 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%